The Impact of the COVID-19 Pandemic on Microfinance Banks Customers in Nigeria - Onuka, Ifeanyi Onwuka; Oroboghae, Ozegbe Roseline (Journal of Asian Business Strategy, 2022)
This study investigated the impact of the Covid-19 pandemic on small businesses, poor individuals and vulnerable households who constitute the majority of customers of microfinance banks (MFBs) in Nigeria. A client survey was conducted by telephone and face to face with a representative sample of clients of MFBs in South West Nigeria for the period from 2019 to 2021. A structured questionnaire, interviews, focus group discussions and participant observation were used to generate the data, while the descriptive statistical analytical method was used to analyze and present the findings. The study reveals that the Covid-19 pandemic and the government-mandated lockdown to curtail the spread have dealt a heavy blow to the incomes of businesses and households of MFB clients in Nigeria. The findings provide practical insights for the Nigerian government and suggests a review of the microfinance scheme to improve its effectiveness.